STRUKTUR DAN FUNGSI SASTRA LISAN â€œBURUDAâ€ DALAM KEHIDUPAN MASYARAKAT GORONTALO - Kadir, Herson; Hinta, Ellyana (Universitas Pendidikan Indonesia, 2020)
Buruda is an oral literary work as a regional cultural asset that is relatively important in the community life of Gorontalo. This research is conducted as an effort to preserve and maintain oral literature as part of the Gorontalo regional folklore. The research is aimed at describing the structure and function of buruda oral literature in the community life of Gorontalo. Moreover, this research applies a qualitative descriptive method, while the data collection technique is done by observation technique through recording and note taking, as well as interview technique that is carried out on informants such as traditional leaders and community leaders. The primary data of this research are buruda verses that have been translated into the Indonesian Language. Then, the data are analyzed structurally to discuss content and form. After that, interpreting, describing, and translating the functions of buruda oral literature are carried out. The research finding revealed that the structures of buruda oral literature are in the form of verse that consisted of ten parts as follows: (1) contains an expression of the feelings of people who are in love; (2) warning of the danger of lust; (3) praise to the prophet Muhammad shallalahu ‘alaihi wa sallam; (4) the birth of the Prophet Muhammad shallalahu ‘alaihi wa sallam as the light and guide to the right way; (5) the miracle owned by the Prophet Muhammad shallalahu ‘alaihi wa sallam; (6) the glory of the Qur’an contains instructions for human salvation in the world and the hereafter; (7) the truth of isra and mi'raj experienced by Muhammad shallalahu ‘alaihi wa sallam; (8) the challenges of the struggle of the Prophet Muhammad shallalahu ‘alaihi wa sallam in spreading the message of Islamic treatises; (9) the importance of avoiding sin and immorality because of ashamed to Allah subhanahu wa ta'ala; (10) the power of prayer and the importance of bermunajat (praying wholeheartedly) asking for mercy and compassion from Allah subhanahu wa ta’ala. Furthermore, the function of buruda oral literature in the community life of Gorontalo contains moral messages in the form of a religious function, ethical function, and cultural function.